SLESS 2.0: uma evolução da abordagem de integração do Scrum e Lean Six Sigma para aplicações móveis - Cunha, Thiago Ferraz Vieira da (2014)
The software development for mobile devices such as mobile phones, smartphones and tablets requires knowledge not only of processes but also related to software and hardware technology platforms of these devices. Continuous improvement in the performance of these platforms and the increasing demand for a variety of applications require a high competitiveness and, therefore, high levels of productivity and quality. In this scenario, agile methodologies are used and fit well to frequently changing requirements and to time to market. Among these methodologies, Scrum is one of the most accepted and used, contributing to the improvement of project management, team productivity, product quality and increasing the probability of project success. On the other hand, there is an increasing adoption of quality management methodologies such as Lean Six Sigma in Information Technology and Communication (ICT) organizations due to their proven results in improving processes development and quality of services and products developed. Methodologies such as Scrum and Lean Six Sigma have different goals, however, they can contribute together in the development of software for mobile devices. In literature, there are studies that propose the integration of agile methodologies and software quality, however, they have gaps regarding the possibility of systematic reuse of this integration, as well as in evaluating the use of these integrated methodologies. Thus, this paper proposes an evolution of an existing approach, called SLeSS, that integrates Scrum to Lean Six Sigma and has been used in the software customization for mobile phones. The evolution of this approach is to add software development in addition to customization and improve integration mechanisms initially proposed with a focus on evaluation of the practices and principles of Scrum from the use of techniques of Lean Six Sigma. This new version is applied in seven actual projects that are related to software development and customization for mobile devices and their results are also discussed in this dissertation.